Emotional Management in Elementary School-Age Children in the Dynamics of Modern Life: Strategies, Challenges, and Solutions - Nadiyah, Nadiyah; Abroto, Abroto; Kahar, Aris Armeth Daud Al; Fadil, Khaidir; Yamkee, Abduhakim Kaje (Profesi Pendidikan Dasar, 2025)
The urgency of this article is the increase in the prevalence of socio-emotional problems faced by elementary school children in the modern era. This study used a Systematic Literature Review (SLR) approach to identify, evaluate, and synthesize critically the empirical findings regarding emotional management in elementary school-age children in the context of modern life. Scientific articles used were those published between 2015 and 2024, and articles indexed in Scopus and Sinta databases. Moreover, studies that explicitly discuss emotional management in 6-12-year-old children were also included. The results of the study indicated that emotional management strategies for children have been developed globally, yet their implementation remains uneven at the local level. Three main findings for effective strategies that frequently emerge are emotional management strategies, with 44 articles (31.65%). Common challenges were reported in 42 articles (30.14%), such as a lack of teacher training in managing students' emotions. Solutions involving teacher training regarding emotion and their regulations were reported in 21 articles (29.19%). This functions as a solid foundation to understand how children's emotional education should be developed, not only taught.